2019
DOI: 10.1113/ep087670
|View full text |Cite
|
Sign up to set email alerts
|

Impaired metabolic and hepatic functions following subcutaneous lipectomy in adult obese rats

Abstract: The number of obese older adults is on the rise, but data about proper treatment of obesity in the elderly is controversial. The present study was designed to investigate the effectiveness and consequences of partial subcutaneous lipectomy, as a rapid medical intervention against increased accumulation of body fat, in adult obese rats. The study was conducted on adult (9-12 months) female rats, in which obesity was induced by bilateral surgical ovariectomy. They were randomized into two main groups: short term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
2
1
0
Order By: Relevance
“…These results are consistent with those of our previous study in which ovariectomy was used to induce obesity in premenopausal rats [ 17 ]. Despite the similarity in net results and study duration, body weight and metabolic changes were more prominent in young rats than in premenopausal rats (Table 3 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with those of our previous study in which ovariectomy was used to induce obesity in premenopausal rats [ 17 ]. Despite the similarity in net results and study duration, body weight and metabolic changes were more prominent in young rats than in premenopausal rats (Table 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…The present data extend and confirm our previous research on the impact of subcutaneous lipectomy in obese premenopausal rats [ 17 ]. The results demonstrated that lipectomy surgery, whether in premenopausal or in young rats, has unfavorable outcomes, including fasting hyperglycemia, disturbed lipid profile associated with atherosclerotic changes in the wall of the abdominal aorta, and impaired liver functions coupled with hepatic cell vacuolation and inflammatory cell infiltration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All the abovementioned substances were evaluated by respective assays produced by "Filisit Diagnistika" (Ukraine). We also calculated body-mass index (BMI) according to recommendations [13].…”
Section: Methodsmentioning
confidence: 99%